Literature Review on Acupuncture Treatment for Parkinson’s Disease - Teng, Le-xus; Yong, Yii Pin; Tang, Freya, Sin Wei (INTI International University, 2024)
Parkinson’s Disease is a degradation of brain functions leads to deterioration in movement, sleep, mental health, pain, memory, self-care, daily activity and other health issues. In modern medicine, treatment of Parkinson’s Disease provided mostly involves symptom control which can lead to side effects. Acupuncture treatment in Traditional Chinese Medicine has been researched to be able to relieve the symptoms, reduce the side-effects caused by medication as well as slowing down the progression of the disease. The objective of this thesis is to review the frequency of acupoint selections as well as meridian used to treat Parkinson’s Disease. In this thesis, all the data are collected from online databases based on the inclusion and exclusion criteria. The data collected will be tabulated and calculated to conclude the result. There were total 46 journals selected and the most frequently appeared acupoints are Bai Hui appeared 27 times, Tai Chong appeared 25 times, He Gu appeared 24 times, San Yin Jiao appeared 21 times, Zu San Li appeared 20 times and Si Shen Cong appeared 20 times which are the top 6 acupoints. Meanwhile Tai Yang Bladder of the Foot (BL) appeared 24 times and Governor Vessel (GV) appeared 20 times were the top 2 meridians that most frequently used. The World Health Organisation (WHO) defines a Sustainable Healthcare System as a system that improves, maintains or restores health, while minimizing negative impacts on the environment and leveraging opportunities to benefit of the health and well-being of current and future generations. In fact, acupuncture treatment can improve the health and well-being of the Parkinson’s disease patient with long term cost savings as a sustainable health care.